Patient Safety Culture in a Teaching Hospital in Eastern Province of Saudi Arabia: Assessment and Opportunities for Improvement - Aljaffary A; Al Yaqoub F; Al Madani R; Aldossary H; Alumran A (Dove Medical Press, 2021)
Afnan Aljaffary,1 Fatemah Al Yaqoub,2 Reem Al Madani,3 Hessa Aldossary,1 Arwa Alumran1 1Department of Health Information Management & Technology; College of Public Health; Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2Risk Management and Patient Safety Department; Dammam Medical Complex, Dammam, Saudi Arabia; 3Risk Management Unit, Directorate of Quality and Safety, King Fahad Hospital of the University, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Afnan AljaffaryImam Abdulrahman Bin Faisal University, King Faisal Road, Dammam, KSA, 34212, Saudi ArabiaTel +9660133338086Email aaljaffari@iau.edu.saPurpose: The objective of the present study is to explore the perceptions of patient safety culture (PSC) among King Fahd University Hospital's (KFUH) employees and to develop recommendations to overcome the factors that impede the integration of PSC in the study setting.Methods: This is a cross-sectional study that assessed the level of PSC at KFUH. This study used the Hospital Survey on Patient Safety Culture tool from all KFUH healthcare workers (n=900) in 2018.Findings: The response rate of the study was 67%. Findings show that KFUH excelled in three PSC composites: continuous organizational learning, feedback and communication about error, and frequency of events reported. In contrast, staffing, teamwork within units, and non-punitive response to error yielded low composite scores.Originality/Value: The strength of the present study was the use of a valid questionnaire that has been used widely in the literature with a large sample size, which yielded valid results. It is, to our knowledge, the first research study that analyzes health workers' perceptions on patient safety culture in a teaching hospital in Eastern Province in KSA and compares it with Agency for Healthcare Research and Quality (AHRQ) and Saudi Hospital Survey on Patient Safety Culture (HSPSC). Results from the study highlight the need to employ an adequate number of workers, implement continuous patient safety training programs, and adopt safety programs and policies.Keywords: patient safety culture, teamwork, non-punitive response to error, hospital survey